Preparation and Color Properties of Pigments Based on YMnO3±δ - Burkovičová Aneta; Dohnalová Žaneta; Šulcová Petra (Česká společnost průmyslové chemie, 2015)
Compounds with general formula YMnx(MA)1-xO3±δ, where x = 0,1; 0,5; 0,9 and 1,0; M = Sn; Ti; Zr and A = Cu or Ni were prepared by mechanical activation and fired in temperature range from 1000 °C to 1200 °C. Color properties were measured by ColorQuest XE (HunterLab, USA) and evaluated in color system CIE L*a*b*. Particle size distribution was measured by Mastersizer 2000/MU (Malvern Instruments Ltd., GB) and phase purity was verified by X-ray diffraction analysis (D8 Advance, Bruker, GB).
Příprava a barevné vlastnosti pigmentů na bázi YMnO3±δ
Keywords: Inorganic Pigments; CIE L*a*b*; YMnO3; anorganické pigmenty; CIE L*a*b*; YMnO3